HUMAN CAPITAL DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF TRANSFORMATIONAL CHANGES IN THE DIGITAL ECONOMY - Птащенко, Олена В.; Шершенюк, Олена М. (Journal of Strategic Economic Research, 2024)
The presented article examines aspects of the development of human capital of agricultural enterprises in the conditions of transformational changes of the digital economy. Today, taking into account the specifics of human capital development can provide special competitive advantages to business entities. It is the process of improving human capital that can become a guarantee of success in the competitive struggle in the conditions of modern transformations and changes. Challenges and opportunities arising in the process of digitalization of the agricultural sector are considered, in particular, the need for new knowledge and skills of employees. The purpose of the presented work is to determine the main components of the development of human capital of agricultural enterprises in the conditions of transformational changes of the digital economy. The main methods of the presented work are: methods of analysis and synthesis to identify the main characteristics of the development of human capital of agricultural enterprises, as well as to determine the components of the influence of the digital economy on the development of human capital; methods of deduction and induction to determine the features of the digital economy and take into account transformational changes for the development of human capital in agricultural areas; comparison method, generalization method, graphical and tabular method for presenting research results. Approaches and strategies for effective human capital development are analyzed, including continuous learning, adoption of digital tools and technologies, and management innovation. The key factors contributing to increasing the competitiveness and sustainability of agricultural enterprises in the digital age are determined. The article provides recommendations on creating a favorable environment for the development of human capital, which is critically important for the successful adaptation and prosperity of the agricultural sector in the conditions of global economic changes.